Organic metal matrix Mil-88a nano-enzyme for joint repair in the osteoarthritis mouse model - Hu, Hao; Huang, Xu; Dai, Yankun; Zhu, Kairun; Ye, Xuwen; Meng, Shengdong; Zhang, Qing; Xie, Xueguan (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Osteoarthritis (OA) is a degenerative joint disease that affects millions of people worldwide. Currently, there is no cure for OA, and existing treatments have limited efficacy. Therefore, novel strategies are needed to overcome OA. Materials and Methods: In this study, we evaluated the potential of a novel nanomaterial strategy using Mil-88a nanozyme loaded onto an organic metal matrix to treat OA in a mouse model. First, we synthesized the Mil-88a nanozyme and assessed its toxicity using the CCK-8 method and live-dead staining. Next, we constructed an OA model in mice and collected paraffin sections of joints for histological evaluation. We used immunofluorescence and immunohistochemistry to identify OA progression and evaluated OA grades using the OARSI score. Results: We observed that Mil-88a could be easily synthesized and had high biocompatibility. Additionally, we found that Mil-88a could significantly promote the expression of OA anabolism-related genes such as Col2 and significantly inhibit the expression of OA catabolism-related genes MMP13. Furthermore, animals treated with Mil-88a nanoenzyme loading on an organic metal matrix had better OARSI scores compared to the non-treated group. Conclusion: Our study suggests that Mil-88a co-loaded with an organic metal matrix could be a promising nanoenzyme strategy to treat OA by improving cartilage regeneration and alleviating the progression of the disease.